2013
DOI: 10.1016/j.apsb.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and ACE inhibitory activity of desert plant Suaeda physophora Pall.

Abstract: Suaeda physophora Pall. is a kind of desert plant mostly growing in saline habitats in Xinjiang Uygur Autonomous Region. In order to have a better utilization of halophytes, a screening for ACE inhibitors from halophytes growing in Xinjiang was carried out. The result showed that the 70% EtOH extract and n-BuOH extract of S. physophora Pall. possessed significant ACE inhibitory activities. So we focused on its biochemical constituents firstly. One new quinazoline alkaloid, namely Suaedine (1), along with six k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…The ACE-inhibitory activity of halophyte extracts has been scarcely reported. Men et al [ 35 ] found lower inhibitory activity (83%, 100 mg/mL) in extracts of Suaeda physophora . These authors attributed the ACE-inhibitory activity to the presence of polyphenols in the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…The ACE-inhibitory activity of halophyte extracts has been scarcely reported. Men et al [ 35 ] found lower inhibitory activity (83%, 100 mg/mL) in extracts of Suaeda physophora . These authors attributed the ACE-inhibitory activity to the presence of polyphenols in the extracts.…”
Section: Resultsmentioning
confidence: 99%
“…Spectral properties of gomphrenin-type betacyanins are listed in The ambiguity in structure elucidation in some cases has been resolved with the use of sophisticated techniques. For example, suaedin was reported as a betacyanin, citryl-celosianin, based on data obtained from paper electrophoresis, paper chromatography, hydrolysis, and silica-gel TLC (Piattelli and Imperato, 1971), but recent report based on HR-ESI-MS, 1 H NMR, 13 C NMR spectra confirmed that the compound was not a betacyanin rather a betacyanin-like (Men et al, 2013). The authors isolated this compound as lilac powder and the structure was elucidated as (10bS,2 0 S)-1,5,6,10b-tetrahydro-8,9[2 0 -(2 00 -hydroxy-00 -carboxylalkenyl)-[1 0 ,3 0 ]-dioxolo]-2H-pyrrolo[2,1-a]isoquinoline-3-one.…”
mentioning
confidence: 89%
“…[ 60 ] Suaeda physophora Pall has isolated a quinoline alkaloids (Suaeda) and flavonoid compounds that also have a potential of ACE inhibitors activity. [ 65 ] The astilbin (with IC 50 of 4.53 mg/mL) were isolated from Erythroxylum gonocladum plant. [ 56 ] The quercetin isolated from Peperomia pellucida L. Kunth herbs with IC 50 of 7.72 mg/mL.…”
Section: Resultsmentioning
confidence: 99%